Sustainable groundwater development in a naturally arsenic-contaminated aquifer: the case of the Cmino-Vico volcanic area (central Italy) - Baiocchi, Antonella; Coletta, Attilio; Espositi, Luca; Lotti, Francesca; Piscopo, Vincenzo (Italian journal of engineering geology and environment, 2013)
This study concerns the occurrence of arsenic in groundwater of the Cimino-Vico volcanic area (central Italy), widely used for drinking water supply and irrigation. The purpose is to provide a hydrogeo- logical support for readdressing the groundwater resource management in order to minimize the presence of the carcinogenic element in tapped waters.The Cimino-Vico volcanic area constitutes a complex hydrogeological system including several perched aquifers and a continuous basal aquifer in the volcanites, in some areas also in uenced by deeprising thermal waters. The occurrence of arsenic in groundwater is connected to the length of circuits in the volcanic rocks and, mainly, to the active hydrothermal system.The published and unpublished data of the arsenic content in groundwater of the basal aquifer were processed to obtain a reviewed map of its distribution, using geostatistical techniques. Results were compared with the present distribution of withdrawal supplying drinking water. The comparison highlights that the present management of groundwater resources does not follow a sustainable approach, with higher rate of withdrawal in areas with arsenic concentration exceeding 10 μg/L, and, vice versa, low rate in areas with lower concentration of the contaminant.The case study highlights that the future options for promoting sustainable water management in a naturally contaminated area are strongly conditioned by the knowledge of the hydrogeological environment. From this knowledge some alternative and/or integrative possibilities to the treatment solutions arise.